USING POLITICAL RIGHTS LEGAL LIABILITY IN SELECT THE OPERATION OF ELECTORAL SHURA (ELECTIONS) IN INDONESIA - Nur’l Yakin Mch (International Journal of Law Reconstruction, 2018)
The increasing number of White Group (Abstentions) in every election in Indonesia which is the country's lack of nomokratic indicates people in using their voting rights. When attempts were made government in various ways such as dissemination of the importance to follow the election, but still a high percentage of non-voters there are indications tend to increase. Not only that, a lot of people who misinterpret and fail to understand what is meant in the legislation on the use of the right to vote in the election, it may be because the law is written textual status right but not the obligation to vote. While the Shura offer an alternative in solving this problem, namely the implementation of laws obligation to choose a leader.